2008
DOI: 10.1016/j.ajog.2008.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Hormones restore biomechanical properties of the vagina and supportive tissues after surgical menopause in young rats

Abstract: Objective-To determine the impact of hormones on the biomechanical properties of the vagina and its supportive tissues following surgical menopause in young vs middle aged rats. Results-OVX induced a rapid decline in the biomechanical properties of pelvic tissues in young but not middle aged rats. Supplementation with E2, E2 + P4, or CMT-8 restored tissues of young rats to control levels with no effect on middle aged tissues. Parity did not impact tissue behavior. Methods-Long-EvansConclusions-OVX has a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 25 publications
3
41
1
Order By: Relevance
“…We have demonstrated that there is a genetic predisposition for developing POP independent of menopause and leuprolide administration which is associated with hypoestrogenism. Current in vitro and animal studies have shown that estrogen has positive effects on the ECM 1517, 20 and others have shown that hypoestrogenism is associated with deterioration of the ECM and development of POP 57,19. The Women’s Health Initiative demonstrated that conjugated equine estrogen alone and conjugated equine estrogen with medroxyprogestesrone increased the risk of urinary incontinence among continent women and worsened the characteristics of urinary incontinence in symptomatic women after 1 year of treatment 37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that there is a genetic predisposition for developing POP independent of menopause and leuprolide administration which is associated with hypoestrogenism. Current in vitro and animal studies have shown that estrogen has positive effects on the ECM 1517, 20 and others have shown that hypoestrogenism is associated with deterioration of the ECM and development of POP 57,19. The Women’s Health Initiative demonstrated that conjugated equine estrogen alone and conjugated equine estrogen with medroxyprogestesrone increased the risk of urinary incontinence among continent women and worsened the characteristics of urinary incontinence in symptomatic women after 1 year of treatment 37.…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, collagen subtypes are altered in the endopelvic fascia, and hormones have been shown to restore the biomechanical properties of the vagina and supportive tissues after surgical menopause in young rats 19,20. Therefore, the influence of menopause on the ECM has been studied looking to determine pathways that estrogen may be involved in the development of prolapse.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this study, five animals per group would be required to achieve statistical significance with a power of at least 80% [6]. Results are represented as mean±SD.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from our laboratory have suggested that, while parity sets the stage, hormones play a role by protecting pelvic soft tissue supportive structures from degradation by matrix metalloproteinases (MMPs). This was demonstrated in the rodent model by showing that hormone therapy (HT) or an MMP inhibitor equally obviated the decline in mechanical integrity following surgical menopause (ovariectomy) [5]. Using vaginal fibroblasts subjected to cyclic stretching from human subjects, this mechanism was further elucidated by showing an increase in active MMP in the presence of stretch and suppression of this response in the presence of hormones [6, 7].…”
Section: Introductionmentioning
confidence: 99%